Integrated assessment models for ecologists: the present and the future. Issue 2 (11th August 2013) - Harfoot, Michael; Tittensor, Derek P.; Newbold, Tim; McInerny, Greg; Smith, Matthew J.; Scharlemann, Jörn P. W.
Abstract Aim Human impacts on the biosphere are a matter of urgent and growing concern, with ecologists increasingly being asked to project biodiversity futures. The Intergovernmental Platform on Biodiversity and Ecosystem Services (IPBES) is likely to comprehensively assess such projections, yet despite being widely used and potentially critical tools for analysing socio‐environmental futures, integrated assessment models (IAMs) have received little attention from ecological modellers. We aim to raise awareness and understanding of IAMs among ecologists by describing the structure and composition of IAMs, assessing their utility for biodiversity projections and identifying limitations that hamper greater interaction between scientists using IAMs and those using ecological models. We also hope to inspire more accessible and applicable models by suggesting development needs for IAMs. Methods We conduct a systematic review of four state‐of‐the‐art IAMs, which describes and contrasts key model features and analyses six aspects of IAMs that are of fundamental interest to ecologists. Conclusions IAMs could be valuable for modelling biodiversity futures; however, current IAMs were not developed for this application and challenges remain for ecologists looking to use their outputs. Separating and understanding the differences resulting from IAM formulation and those resulting from specific scenario assumptions is currently problematic, and current IAMs may be unable to accurately represent environmental conditions for both Earth‐system projections and for building robust models of biodiversity because key ecological processes are absent. We suggest that model intercomparisons would identify differences in model dynamics, and detailed studies of how dynamical interactions between components influence behaviour would address why such differences arise. Bio‐economic fisheries models and agriculture pollination models provide starting points for integrating key ecological feedbacks within IAMs. Ultimately, making IAMs more accessible within the multidisciplinary study of global change, drawing on user‐centred research, would enable more resolved, reliable and accurate assessment of how Earth's socio‐ecological system is approaching planetary boundaries.